On the theory of hyper-Q-homeomorphisms - Kovtonyuk, D. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We show that if a homeomorphism f of a domain D ⊂ R^n, n ≥ 2, is a hyper-Q-homeomorphism with Q ∈ L_loc^1 , then f ∈ ACL. As a consequence, this homeomorphism has partial derivatives and an approximation differential almost everywhere.